Extracellular vesicles in the breast cancer brain metastasis: physiological functions and clinical applications - Sakamoto, Yuima; Ochiya, Takahiro; Yoshioka, Yusuke (Frontiers in Human Neuroscience, 2023)
vesicles, breast cancer brain metastasis, blood-brain barrier, biomarker, exosomes Breast cancer, which exhibits an increasing incidence and high mortality rate among cancers, is predominantly attributed to metastatic malignancies. Brain metastasis, in particular, significantly contributes to the elevated mortality in breast cancer patients. Extracellular vesicles (EVs) are small lipid bilayer vesicles secreted by various cells that contain biomolecules such as nucleic acids and proteins. They deliver these bioactive molecules to recipient cells, thereby regulating signal transduction and protein expression levels. The relationship between breast cancer metastasis and EVs has been extensively investigated. In this review, we focus on the molecular mechanisms by which EVs promote brain metastasis in breast cancer. Additionally, we discuss the potential of EV-associated molecules as therapeutic targets and their relevance as early diagnostic markers for breast cancer brain metastasis.